More than a duologue: In-depth insights into epitranscriptomics and ferroptosis - Cheung, Justin Chak Ting; Deng, Guangzheng; Wong, Nathalie; Dong, Yujuan; Ng, Simon Siu Man (Frontiers in Cell and Developmental Biology, 2022)
Beyond transcription, RNA molecules are enzymatically modified to influence the biological functions of living organisms. The term “epitranscriptomics” describes the changes in RNA strands aside from altering the innate sequences. Modifications on adenosine (A) are the most widely characterized epitranscriptomic modification, including N6-methyladenosine (m6A), N1-methyladenosine (m1A), polyadenylation, and adenosine-to-inosine (A-to-I) RNA editing, and modifications on other nucleotides seem to be fewer, such as N7-methylguanosine (m7G), 5-methylcytosine (m5C), and pseudouridine (Ψ). These changes on the RNA strand surface, exclusively by their RNA-modifying proteins (RMPs), are reported in various biological phenomena, including programmed cell death (PCD). One necro-biological phenomenon that has been observed for long but has started to gain heed in recent years is “ferroptosis.” The phospholipid peroxidation by polyunsaturated-fatty-acid-containing-phospholipid hydroperoxyl (PLOOH) radicals destroys membrane integrity due to a series of mechanisms. The Fenton reaction, constituting the final Haber–Weiss reaction that is less recognized, collaboratively leading to the conversion of polyunsaturated fatty acid (PUFA) to PLOOH, is the etymological origin of ferroptosis. However, it is with increasing evidence that ferroptotic signaling is also intervened by epitranscriptomic modifications, although the truth is still ambiguous. We attempted to delineate some up-to-date discoveries on both epitranscriptomics and ferroptosis, bringing up the fundamentals to address any potential connection between the two. Next, we discussed whether a duologal relationship, or more, exists between the two, taking the ROS level and iron status into consideration. Lastly, we surveyed future perspectives that would favor the understanding of these topics.